Application of TPM at manufacturing industry : process of centrifugal machine - Mohammad Zuhaidi Omar (School of Manufacturing Engineering, University Malaysia Perlis, 2010)
Total Productive Maintenance (TPM) is a maintenance program which in volves a newly defired concept for maintaining plants and equipment. The goal of the TPM program is to markedly increase production while, at the same time, increasing employee morale and job satisfaction.